2005
DOI: 10.1590/s1516-89132005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Spore production of Beauveria bassiana from agro-industrial residues

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 12 publications
2
16
0
4
Order By: Relevance
“…After the submerged fermentation of I. fumosorosea, Rayati et al (2001) obtained 4.5 × 10 9 spores.g -1 biomass by stationary phase nutrient condition (surface system for sporulation) over 120 h. This result was 4-times higher than the conidia production achieved by the best solid media for ESALQ1296 and ESALQ1205. Another study using agro-industrial residues revealed that the proportion of 60% potato refuse and 40% sugarcane bagasse promoted high production of aerial conidia of B. bassiana (3.4 × 10 9 conidia.g -1 dry mass) in Erlenmeyer flasks (Santa et al, 2005), demonstrating the feasibility of these byproducts as alternative nutritional sources to produce entomopathogenic fungi. 3 Solid medium composition: WR = whole rice, BR = broken rice, MR = milled rice, BC = broken corn, WG = wheat grain, RH = rice husk, SM = soybean meal, SB = sugarcane bagasse.…”
Section: Resultsmentioning
confidence: 98%
“…After the submerged fermentation of I. fumosorosea, Rayati et al (2001) obtained 4.5 × 10 9 spores.g -1 biomass by stationary phase nutrient condition (surface system for sporulation) over 120 h. This result was 4-times higher than the conidia production achieved by the best solid media for ESALQ1296 and ESALQ1205. Another study using agro-industrial residues revealed that the proportion of 60% potato refuse and 40% sugarcane bagasse promoted high production of aerial conidia of B. bassiana (3.4 × 10 9 conidia.g -1 dry mass) in Erlenmeyer flasks (Santa et al, 2005), demonstrating the feasibility of these byproducts as alternative nutritional sources to produce entomopathogenic fungi. 3 Solid medium composition: WR = whole rice, BR = broken rice, MR = milled rice, BC = broken corn, WG = wheat grain, RH = rice husk, SM = soybean meal, SB = sugarcane bagasse.…”
Section: Resultsmentioning
confidence: 98%
“…17) In this context, efficient utilization of agro-industrial residues as carbon sources has been shown for the mass production of entomopathogenic fungi. [18][19][20][21] However, the absence of free water induces parameter variations (such as pH, temperature, moisture, dissolved oxygen or CO 2 ) that are difficult to control. A complementarity method between solid-and liquid-state fermentations has been attempted in sequential culture.…”
Section: Introductionmentioning
confidence: 99%
“…Several agro-industrial wastes (refused potatoes, coffee husks and sugarcane bagasse) have been used in SSF to produce spores from Beauveria bassiana to obtain biopesticides for biocontrol of pests of banana, sugarcane, soybean, and coffee (Santa et al, 2005). Colletotrichum truncatum is another fungus that has been studied under SSF and that possesses characteristics to be used as mycoherbicide against the difficult weed Sesbania exaltata (Pandey et al, 2000b).…”
Section: Bioinsecticidesmentioning
confidence: 99%